WIRAUSAHA DALAM MENCIPTAKAN LAPANGAN KERJA - Dominggus Parety; Junus Kwelju (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
Limited employment opportunities make people look for shortcuts to survive, such as criminal acts of theft and extortion against someone. By looking at this situation, the government must find the best solution to solve the unemployment polemic in its country. One of the direct and indirect employment problems is that the workforce increases quickly and in high numbers, while the available job opportunities are very limited, which will lead to unemployment. The number of job seekers in Indonesia is increasing from year to year but is not accompanied by an increase in the number of jobs. This will be related to other problems such as income inequality, poverty, slowing economic growth, urbanization and political instability. Maluku Indonesian Christian University is one of the universities in Maluku Province as a higher education institution that always prioritizes good quality education so that the graduates produced are truly able to answer various challenges and needs of society. For this reason, UKIM's vision is: To become an inclusive, independent, quality university in developing science, technology and art for the welfare of island communities based on faith, knowledge and love. Mission: Organizing the tri dharma of quality higher education at all levels, in order to produce graduates who are able to compete in the job market. Organizing superior educational programs in accordance with the context of island communities in order to improve the welfare of the community. This research is qualitative in nature to explain entrepreneurship in creating jobs. Data obtained through research conducted qualitatively, the research uses supporting theories as a basis and is linked to field data obtained and the current societal context. The results obtained can be seen that among students on the UKIM campus their interest in entrepreneurship can still be said to be very minimal. Only around 40% of the 4,842 students are involved in the world of entrepreneurship.